RESULTS OF STRUCTURAL AND PALEOMAGNETIC INVESTIGATIONS OF JURASSIC AND CRETACEOUS COMPLEXES IN THE MESOZOIDES OF NE RUSSIA - Aleksyutin M.V.; Bondarenko G.E.; Minyuk P.S. (My University, 2001)
This paper examines the results of comprehensive structural (structural-geometric analysis of plane elements and kinematic analysis of faults and associated shear fractures) and paleomagnetic data for Jurassic rocks of the Elekchan graben, Omulevka block, northern part of the Sugoi fold zone, Korkodon zone of the Omolon massif, and also Upper Cretaceous assemblages of the Ola segment of the Okhotsk-Chukotka volcanogenic belt (Ola Bay in Magadan area). Materials obtained from structural investigations aided recognition of a multistage structural evolution of the Elekchan graben that bears features of pulsation strike-slip-line deformations. Features of post-Jurassic strike-slip-line deformations have been ascertained for the western periphery of the Omolon massif and the northern part of the Sugoi zone, which are attended by sinistral rotation of small blocks. Post-Turonian strike-slip-line deformations have been identified for the Ola segment of the Okhotsk-Chukotka belt, which could be attended by dextral rotation of blocks. With reference to paleomagnetic data, post-Jurassic lateral movements of the studied assemblages on the amplitude did not exceed the accuracy limits of the paleomagnetic methods. A wide age range has been established for deformations linked to the Verkhoyansk phase of folding: From the Middle Jurassic on the west of the Omolon massif to Kimmeridgian-Volgian ages on the east of the Omulevka high. Paleolatitude characteristics for the pre-fold component of the studied structures and areas do not differ significantly from those for Siberia (areas and structures of the eastern part of the Kolyma structural loop) and North America (Ola segment of the Okhotsk-Chukotka belt).
Keywords: Cretaceous; Jurassic; Okhotsk-Chukotka volcanogenic belt; structural and paleomagnetic data; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая; Mesozoic::Cretaceous